Is Income Discrimination a Factor in the Recent Venezuelan Migration? - Guillen, Jorge (2023)
The following paper analyzes income discrimination during the recent Venezuelan migration in Peru. We use the survey “Encuesta Dirigida a la Población Venezolana (ENPOVE)” in order to proceed with our assessment. The ENPOVE surveys were conducted in 2018 with 9,487respondents (3,611 houses).The survey enabled the collection of socioeconomic variables and discrimination perceptions of Venezuelan residents in Tumbes, La Libertad, Arequipa, Cusco, Lima, and Callao. The results allow us to investigate the Peruvian labor market for low-skilled immigrant workers.